The mammalian skeletal muscle DHPR has larger Ca2+ conductance and is phylogenetically ancient to the early ray-finned fish sterlet (Acipenser ruthenus). (January 2017) - Schrötter, Kai; Dayal, Anamika; Grabner, Manfred
Graphical abstract: Highlights: Ca 2+ conductivity of sterlet DHPR is significantly reduced compared to rabbit. Skeletal muscle DHPR of the "living fossil" sterlet is more evolved than of rabbit. In contrast to zebrafish the DHPR of sterlet is still Ca 2+ conducting. Abstract: The L-type Ca 2+ channel or dihydropyridine receptor (DHPR) in vertebrate skeletal muscle is responsible for sensing sarcolemmal depolarizations and transducing this signal to the sarcoplasmic Ca 2+ release channel RyR1 via conformational coupling to initiate muscle contraction. During this excitation-contraction (EC) coupling process there is a slow Ca 2+ current through the mammalian DHPR which is fully missing in euteleost fishes. In contrast to ancestral evolutionary stages where skeletal muscle EC coupling is still depended on Ca 2+ -induced Ca 2+ -release (CICR), it is possible that the DHPR Ca 2+ conductivity during mammalian (conformational) EC coupling was retained as an evolutionary remnant (vestigiality). Here, we wanted to test the hypothesis that due to the lack of evolutionary pressure in post-CICR species skeletal muscle DHPR Ca 2+ conductivity gradually reduced as evolution progressed. Interestingly, we identified that the DHPR of the early ray-finned fish sterlet ( Acipenser ruthenus ) is phylogenetically positioned above the mammalian rabbit DHPR which retained robust Ca 2+ conductivity, but below the euteleost zebrafish DHPR which completely lost Ca 2+ conductivity. Remarkably, our results revealed that sterlet DHPR still retained the Ca 2+ conductivity but currents are significantly reduced compared to rabbit. This decrease is due to lower DHPR membrane expression similar to zebrafish, as well as due to reduced channel open probability (Po ). In both these fish species the lower DHPR expression density is partially compensated by higher efficacy of DHPR-RyR1 coupling. The complete loss of Po in zebrafish and other euteleost species was presumably based on the teleost specific 3rd round of genome duplication (Ts3R). Ts3R headed into the appearance of two skeletal muscle DHPR isoforms which finally, together with the radiation of the euteleost clade, fully lost the Po .